Control complex for a double-sided microstrip detector production and tests - Kaplij, A.A.; Kulibaba, V.I.; Kuijer, P.; Maslov, N.I.; Ovchinnik, V.D.; Potin, S.M.; Starodubtsev, A.F. (Вопросы атомной науки и техники, 2000)
The controlling system for detector silicon and for a double-sided microstrip detectors (DSMD) characteristics tests is described.